The Influence of Social Capital and Human Capital on Food Security in Karangpatihan Village, Indonesia - Miranti, Nikita Rahma; Dinanti, Dian; Zahid, Umair; Khan, Reesha; Suhartini, Wildan (Fakultas Teknik Universitas Brawijaya, 2024)
Agriculture is vital to food security because it provides food, clothing, and shelter. Based on the 2022 Indonesian Food Security Index (IKP), Ponorogo Regency is ranked 19th out of 416 districts throughout Indonesia, with a food security score of 86.20. However, there will be a decline in rice production in Ponorogo Regency in 2022. It will, of course, impact the condition of food security in villages, one of which is Karangpatihan Village. Social capital is a fundamental aspect of creating sustainable agricultural development. This concept refers to the beliefs, networks, values, and norms facilitating cooperation and collective action to achieve common goals. The strong trust between farmers is vital to fostering cooperation and strengthening their social networks. A good social network reflects mutually agreed-upon norms for establishing relationships and interacting. This research aims to identify the influence of farmers' social and human capital in supporting food security in Karangpatihan Village. Research data was obtained based on questionnaires from 250 farmers in Karangpatihan Village. The analysis used is structural equation modeling (SEM) analysis, which is used to identify the influence between variables. Based on SEM analysis, there is a positive direct relationship between social capital and food security variables. Meanwhile, the direct relationship between human capital and food security variables is negative.